A new species of Eucapnopsis (Plecoptera: Capniidae) from China - Cao, Zhishan; Yang, Ding; Li, Weihai (Zootaxa, 2020)
A new species of Capniidae, Eucapnopsis yunnana sp. nov., is described and illustrated from Yunnan Province, southwestern China. The relationships with other similar species of the genus are discussed.